The Influence of Financial Literacy, Self-Control, and Peer Environment on Financial Management in Gen Z in Selong City - Nurul Arma Rohayanti; Qurratul Aini; Pahrudin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to determine the effect of financial literacy, self-control, and peer environment on the financial management of Generation Z in Selong City. This research uses a quantitative approach with a causal associative research design that aims to understand the relationship and influence between two or more variables. The sampling technique used is purposive sampling with a total sample of 100 respondents. The data analysis technique employs multiple linear regression analysis using SPSS version 22. The results of this study indicate that financial literacy has no significant effect on financial management. Self-control has a positive and significant effect on financial management. The peer environment also has a positive and significant effect on financial management. Simultaneously, financial literacy, self-control, and peer environment have a significant effect on financial management..